Faktor-Faktor Penyebab Kurangnya Minat Belajar Siswa Kelas Dua Belas Pada Pembelajaran Pendidikan Agama Kristen di Sekolah Menengah Kejuruan Negeri 1 Modoinding Dan Cara Menanggulanginya - Marde Christian Stenly Mawikere (Jurnal Ilmiah Wahana Pendidikan, 2020)
This iarticle iis ia istudy iof ithe ifactors ithat icause ithe istudents' ilack iof iinterest iin ilearning iin iclass iXII iin ilearning iChristian ireligious ieducation i(PAK) iat iSMK iNegeri i1 iModoinding iand ihow ito iovercome ithem iin ithe iperiod ifrom iJanuary i2021 ito iJune i2021. Based ion ithe iresults iof iresearch iwith ia iqualitative iapproach iwhich iwas icarried iout ithrough idata icollection imethods iusing iobservations iand iinterviews, iobtaining iprocessed idata iand ianalysis iof ithe icontext iof iPAK ilearning iat iSMK iNegeri i1 iModoinding iwas inot imaximized ibecause iteachers iwere iless icreative iand iinnovative iin ichoosing iand iapplying ialternative imethods. ilearning. iLikewise, ithe ilearning iprocess iis imore iteacher-centered, icausing ino istimulus iand istudent iresponse ito ihave ian iincreased iinterest iin ilearning ibecause ithe iclassroom iatmosphere iis imonotonous. iAnother ifactor iis ithe ilimited iparenting istyle ifor istudents. iThis istudy ialso ishows ithat ithere iare iinternal ifactors ithat iinfluence istudents' iinterest iin ilearning, inamely imotivation iwithin istudents ithemselves. The ifinal iresult iof ithis istudy ishows ihow ito iovercome ithe ilack iof istudent iinterest iin ilearning, inamely ithe iuse iof icreative, iinnovative iand ivaried imedia iand ilearning imethods ifrom iteachers iwho imust ialso ibe isupported iby ieffective iparenting istyles ias iwell ias ithe icharacter iand imotivation ithat icomes ifrom ithe istudents ithemselves.